2004
DOI: 10.1007/s00198-004-1604-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional limitations and poor physical performance as independent risk factors for self-reported fractures in older persons

Abstract: Objective: This study examined whether three aspects of functioning (i.e., functional limitations, physical performance, and physical activity) were associated with fractures in older men and women. Design: A 3-year prospective cohort study. Participants and setting: A total of 715 men and 762 women, aged 65 years and older, of the population-based Longitudinal Aging Study Amsterdam. Measurements: During an interview at home, three aspects of functioning were assessed: functional limitations (what people say t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
4

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 34 publications
4
37
0
4
Order By: Relevance
“…The walking test is an indicator of coordination, proximal muscle strength and balance; the chair stands test is an indicator of proximal muscle strength; and the tandem stand is an indicator of balance (Wicherts et al, 2007). Physical performance, especially walking speed, has been associated with multiple negative health outcomes (Guralnik et al, 1994;Stel et al, 2003Stel et al, , 2004Ostir et al, 2007;Hamer et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The walking test is an indicator of coordination, proximal muscle strength and balance; the chair stands test is an indicator of proximal muscle strength; and the tandem stand is an indicator of balance (Wicherts et al, 2007). Physical performance, especially walking speed, has been associated with multiple negative health outcomes (Guralnik et al, 1994;Stel et al, 2003Stel et al, , 2004Ostir et al, 2007;Hamer et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Physical performance decreases with aging and is associated with multiple negative health outcomes, such as cardiovascular disease (Hamer et al, 2009), falls and fractures (Stel et al, 2003(Stel et al, , 2004, nursing home admission and mortality (Guralnik et al, 1994;Ostir et al, 2007). Five previous studies observed associations between elevated homocysteine and lower physical performance in the general older population (Kado et al, 2002;Soumare et al, 2006;Gerdhem et al, 2007;Kuo et al, 2007;Rolita et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Self-reported activity limitations were assessed with a validated questionnaire concerning the degree of difficulty with the following six activities of daily living: climbing stairs, walking 5 min outdoors without resting, getting up and sitting down in a chair, dressing and undressing oneself, using own or public transportation, and cutting one's own toe nails (26). Participants reported a score of zero (not any difficulty) to six (difficulty with all activities).…”
Section: Physical Functionmentioning
confidence: 99%
“…Participants reported a score of zero (not any difficulty) to six (difficulty with all activities). The number was dichotomized to the presence of none or one activity limitation or the presence of two or more activity limitations (26). Two or more activity limitations are more likely to be due to an underlying disease than one activity limitation.…”
Section: Physical Functionmentioning
confidence: 99%
“…Prolonged inactivity and immobility lead to bone loss and muscle weakness and subsequent decline in physical functioning, with increased risks of falls and fractures (DiPietro 2001;Stel et al 2004;Visser et al 2005;Booth et al 2011). Hence, a downward spiral becomes apparent.…”
Section: Introductionmentioning
confidence: 99%